Rachunek kosztów w publicznym zakładzie opieki zdrowotnej na przykładzie Śląskiego Centrum Chorób Serca - Skrzypczak, Zofia; Szewczyk, Marta; Zembala, Marian (Cost Account in a Public Health Care Institution on the Example of Reports of the Silesian Center of Heart Diseases, 2008)
The article presents changes implemented to cost account in the Silesian Center of Heart Diseases between 1997 and 2004. New local regulations - the Ministry of Health ordinance, which became the major driver of the change, introduced strict rules regarding profit and loss account. Current methods of cost account in health care institutions should enable precise calculation of costs incurred on particular patients and, subsequently, cost of treatment of particular clinical entities. The authors analyzed direct and indirect costs borne by public health care institutions. Additionally, they demonstrated the average cost of hospitalization, hospital bed and daily cost of treatment and hospitalization, including average outlays on particular medical procedures in the Silesian Center of Heart Diseases between 1999 and 2004.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 36, s. 165-175